Cybercriminal networks: origin, growth and criminal capabilities - Leukfeldt, E. R. (Eleven International Publishing, 2016)
This book is about cybercriminal networks that make use of digital means, such as phishing, malware or hacking, to steal money from customers of financial institutions. The author analyzes the processes of origin and growthand criminal capabilities, and puts forward several explanations for the differences found between traditional criminal networks and cybercriminal networks.His most important findings are that although the majority of these cybercriminal networks still rely on real-world social ties for their origin and growth, some networks make full use of the advantages that digitization provides. As a new kind of offender convergence setting, forums provide a fluid form of cooperation, making dependency relationships seen in traditional criminal networks less important. Furthermore, examples were found of prolonged, repeated interaction through online communities, which raises the question to what extent digital social ties differ from their real-world counterparts.This study forms an important evidence-based contribution to the criminological knowledge about cybercriminal networks. Furthermore, based on the empirical results, the author outlines possibilities for situational crime prevention against cybercriminal networks. This book will therefore be of interest both to academics and practitioners in the field of cybercrime and cyber security